Legal Protection for Foreign Investors in Tourism Business Development in Bali Province - Made Bayu Sucantra (Journal Equity of Law and Governance, 2025)
Foreign investment has an important role in encouraging regional economic development in Indonesia, such as infrastructure, employment, technology transfer, and economic diversification. As is known, foreign investment in the Province of Bali continues to increase, which makes the Province of Bali one of the factors that encourage regional economic growth in the State of Indonesia. The problems raised from this paper are: 1) Factors of foreign investors' problems with Foreign Investment (FDI) in the Province of Bali; 2) Countermeasures/handling of Foreign Investment (FDI) problems and legal protection for foreign investors in the Province of Bali. This research includes doctrinal research, which is defined as research using analytical and deductive reasoning to interpret and criticize legal material, which seeks to develop legal theories or concepts by examining and comparing legal doctrines, principles, and precedents. This study uses primary, secondary and tertiary data. This study also uses several approaches to provide clarity about the description of the substance of scientific work. The approach in question is a factual approach and a conceptual approach. The results of this study are in general; it can be concluded that the factors that can affect Foreign Investment (FDI) in Bali Province include the following: Economic growth; Domestic interest rates; The exchange rate of the rupiah against foreign currencies; Export; Workers' wages; Economic crisis. So, of course, it is hoped that Bali Province can carry out regulatory reforms, increase political stability, and improve the skills of local workers. It is hoped that the pace of foreign investment can be controlled and the goal of helping regional economic development in Bali Province can be realized.